Walking the Talk: Promoting Middle School Philosophy by Embracing Student Voices - Rick Marlatt (Middle Grades Review, 2018)
This practitioner perspective responds to recent scholarship calling for reinvigorating middle level education by suggesting that the purposeful inclusion of student voices in collaborative learning activities can help educators champion the academic and social growth of early adolescents. The recent practicum experience of a preservice candidate who prioritized the voices of her students illustrates the promotion of democratic education, innovation, and social justice in middle level education.
Keywords: middle school philosophy; student talk; student voices; middle level education